Melalui Model Teaching at Right Level ( TARL) Metode Pemberian Tugas untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Mata Pelajaran Prakarya dan Kewirausahaan KD. 3.2 /4.2 Topik Perencanaan Usaha Pengolahan Makanan Awetan dari Bahan Pangan N - Susan Dewi Cahyono (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2022)
This study aims to see and analyze the increase in motivation and learning outcomes of students in the Craft and Entrepreneurship on the topic Business Planning for Preserved Food Processing from Vegetable Foods through the Teaching at Right Level (TaRL) model for the giving assignment method in class X.MIA.3 MAN 2 Payakumbuh in the Even Semester of the 2021/2022 Academic Year. This research was conducted using the Classroom Action Research method which consisted of two cycles, where each cycle consisted of: planning, action, reflection, and evaluation. This research was conducted from January s.d. March 2022. Data is processed in each cycle and then analyzed using percentages. The results obtained from the Teaching at Right Level (Tarl) model research, the Assignment Method, can increase students' motivation and learning outcomes. This is evident from the increase in student motivation from the average to low level 75% categorized as good in cycle I, in cycle II it rose to 83% in good category, medium level 74% in good category in cycle I, in cycle II rose to 76% in good category. good, high level 79% is categorized as good in cycle I, in cycle II it rises to 74% in good category. The results of learning knowledge of Craft and Entrepreneurship for low levels on average increased from 65% in Cycle I to 80% in cycle II, for high level the average increased from 63.29% in the first cycle to 66.71% in the second cycle, for the high level the average increased from 73.16% in the first cycle to 74.74% in the second cycle. While the learning outcomes skills for the low level on average increased from 75% in the first cycle in good category rose to 90%, the average level increased from 82.86% in the first cycle in good category rose to 85.71%, the average high level increased from 95.79 p there is a good category in the first cycle rose to 95.79%, in the good category in the second cycle. The conclusion obtained from this study is that the use of a scientific approach to the Teaching at Right Level (Tarl) model of the assignment method can increase students' motivation and learning outcomes.